Karakterisasi Minyak Hasil Pirolisis Berbahan Dasar Limbah Plastik Jenis Polypropylene (PP) - Adoe, Dominggus G. H.; Satria, Devi Yola; Sanusi, Arifin (Universitas Nusa Cendana, 2023)
This research was conducted to determine the characteristics of plastic waste pyrolysis oil and compare it with the characteristics of gasoline. The things studied included the physical and chemical properties of pyrolysis oil. The physical properties studied included viscosity and density, while the chemical properties were the heating value. The research was conducted using Polypropylene (PP) plastic, the reactor used was a single reactor with the reactor temperature set at 300 and 3500C. The results showed that the calorific value of pyrolysis oil was 0.194068464 J – 0.209067264 J, the density was 0.7941 – 0.8083 kg/l and the viscosity was 0.9500151572 cPs - 0.9651967743 cPs.